Analisis Nilai Tambah Usaha Home Industry Pengolahan Kopi Tolaki di Desa Tridana Mulya Kecamatan Landono - Punde, Marvani; Geo, La Ode; Gafaruddin, Abdul; Rianse, Ilma Sarimustaqiyma (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
The objective of this research is to (1) determine the processing and marketing channel Tolaki ground coffee 2) to determine the added value of Tolaki coffee at Tridana Mulya Village, subdistrict of Landono. Choosing the research location intentionally in consideration that Industry of Kopindo Sukses Bersama is the only one industry that produce ground coffee at Tridana Mulya Village and also the process using traditional method  result  the different flavor between the others. Analysed method that used  objective  the qualitative analysis, the objective  and Hayami method. Result of the research show that : (1) marketing channels Tolaki coffee there are two channels, namely channel I: Producers - Consumers and channel II: Manufacturer - Retailer - Consumer. (2) The added value created by Tolaki coffee processing activitiesis   Rp. 55.949 / kg of raw materials fort wenty times the production process in one month with a value-added ratio of 62%.